Role of Aliskiren on Arterial Stiffness and Endothelial Function in Patients With Primary Hypertension - Bonadei, Ivano (J Clin Hypertens (Greenwich), 2014)
Arterial stiffness and endothelial dysfunction are important determinants of cardiovascular events in patients with arterial hypertension. There are few data regarding the role of aliskiren on the central hemodynamics and endothelial function in patients with uncontrolled arterial hypertension. The aim of this study was to assess the addition of aliskiren to other antihypertensive drug treatment for arterial stiffness and endothelial function. Thirty uncontrolled hypertensive patients (mean age, 60.4±12.2 years), without any other cardiovascular risk factors, were enrolled. Augmentation index (AIx) and carotid‐femoral pulse wave velocity (cfPWV) by applanation tonometry and reactive hyperemia peripheral arterial tonometry (RH PAT) index using peripheral arterious tonometry at baseline and after 6 months of aliskiren titrated to 300 mg once a day was evaluated. The addition of aliskiren had no effect on values of central AIx (33.26±10.74% vs 28.86±10.74%; P=.36) but did significantly improve values of cfPWV (9.36±2.65 m/s vs 8.72±2.48 m/s; P=.04) and RH PAT index (1.64±0.57 vs 1.75±0.45; P=.05). In addition to improving systolic and diastolic blood pressure, the addition of aliskiren to concomitant antihypertensive drugs in uncontrolled hypertensive patients may be effective in improving aortic stiffness and endothelial function. These results encourage further studies to evaluate the use of aliskiren for cardiovascular prevention.